1/3n-1n=3

Simple and best practice solution for 1/3n-1n=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/3n-1n=3 equation:



1/3n-1n=3
We move all terms to the left:
1/3n-1n-(3)=0
Domain of the equation: 3n!=0
n!=0/3
n!=0
n∈R
We add all the numbers together, and all the variables
-1n+1/3n-3=0
We multiply all the terms by the denominator
-1n*3n-3*3n+1=0
Wy multiply elements
-3n^2-9n+1=0
a = -3; b = -9; c = +1;
Δ = b2-4ac
Δ = -92-4·(-3)·1
Δ = 93
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-9)-\sqrt{93}}{2*-3}=\frac{9-\sqrt{93}}{-6} $
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-9)+\sqrt{93}}{2*-3}=\frac{9+\sqrt{93}}{-6} $

See similar equations:

| 100,000,000,000x200,000,000,000= | | 1/2x-3=2/3x+7 | | 12x-9=4x-3 | | 0=x^2+8x+17 | | x-0.4x=36 | | M^2+5m+1=m-2 | | -4x+10=-6-4 | | 3^(7x+2)-5=19 | | 5(x-2=3(x+4 | | 3(3x+8)=96 | | 3n-3n+5=21 | | 3(1x+1)-7=4 | | 5x2+-28x+-12=0 | | 35-5n=7(6n+5) | | 3(x+1)-7=4 | | 9c–4c+24=-6 | | 40+x=3x-10 | | 2(14+4x)=-44 | | 8x+14=5x-13 | | 5x²+14x-24=0 | | -11x-17=39 | | f-31/6=8 | | 3(j-68)=24 | | (x−18,2)+0,33=4,4 | | (x−18,2)+0,33=4,4. | | C(50)=0.65x+6 | | h+26/6=9 | | 2^3x-7=6^x+2 | | h-6=27 | | 16=10/3x | | h-6=17 | | 6x^2=378 |

Equations solver categories